Temporal expression of MOF acetyltransferase primes transcription factor networks for erythroid fate - Rodrigues, Cecilia Pessoa; Herman, Josip Stefan; Herquel, Benjamin; Valsecchi, Claudia Isabelle Keller L.; Stehle, Thomas; Gruen, Dominic; Akhtar, Asifa (Science Advances, 2020)
Self-renewal and differentiation of hematopoietic stem cells (HSCs) are orchestrated by the combinatorial action of transcription factors and epigenetic regulators. Here, we have explored the mechanism by which histone H4 lysine 16 acetyltransferase MOF regulates erythropoiesis. Single-cell RNA sequencing and chromatin immunoprecipitation sequencing uncovered that MOF influences erythroid trajectory by dynamic recruitment to chromatin and its haploinsufficiency causes accumulation of a transient HSC population. A regulatory network consisting of MOF, RUNX1, and GFI1B is critical for erythroid fate commitment. GFI1B acts as a Mof activator which is necessary and sufficient for cell type-specific induction of Mof expression. Plasticity of Mof-depleted HSCs can be rescued by expression of a downstream effector, Gata1, or by rebalancing acetylation via a histone deacetylase inhibitor. Accurate timing and dosage of Mof expression act as a rheostat for the feedforward transcription factor network that safeguards progression along the erythroid fate.
CRIS-Team Scopus Importer:2023-03-23